anonymous
  • anonymous
what is 7-y-y=-1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
theEric
  • theEric
It's an equation; would you like to know what exact number y is?
anonymous
  • anonymous
-y-y=-1-7 -y^2=-8 -(y^2=8) \[\sqrt{y}=\sqrt{8}\] y= \[2\sqrt{2}\]
theEric
  • theEric
was this \[7-y-y = -1\]or\[7*(-y)*(-y)=-1\]\[7-y*(-y) = -1\] ? I have to know before I go on!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

theEric
  • theEric
@Veneria (-y) - y, or (-y) + (-y), is actually 2(-y). It can also be written as -2(y) or -2y.
theEric
  • theEric
I don't know if you wanted to know what y is or not, but I'll help, just in case. You start with\[7-y-y=-1\] and now I'll add y to both sides, twice. I hope you're familiar with the concept of adding something to both sides. The overall point is that you change both sides in the same way - so that if they are equal before (like they are) then they are still equal after. That way you know your equation is correct. Variable values don't change, so they are the same in the new equation as well. I go from what I had before, to:\[7-y-y+y+y=(-1)+y+y\]\[=\] and y+y is 2 y's added together. That means y+y = 2*y. That's another way of writing it :) So I'll do that, make it happen.\[7=(-1)+2y\] And subtract (-1) from both sides. I could also add 1, because that makes more sense, but I won't. This way you see more algebra; I'm subtracting a negative number. It's hard to get your head around, but it's actually adding that number. \[7-(-1)=(-1)-(-1)+2y\]\[=\]\[7+(+1)=(-1)+(+1)+2y\]\[=\]\[7+1=(-1)+1+2y\]\[=\]\[8=2y\] Now divide both sides by 2..... I have to go. Good luck!

Looking for something else?

Not the answer you are looking for? Search for more explanations.